Review of hemodialysis for nurses and dialysis personnel - Judith Z. Kallenbach (St. Louis, Missouri : Elsevier, Mosby, 2012)
Provides an introduction to dialysis and a review for the certification exam. This title assumes no prior knowledge of patient care, nursing procedures, or dialysis principles, using a question-and-answer format to discuss the basic principles, basic diseases, and basic problems found in the treatment of kidney patients by dialysis.
Hemodialysis team -- History of dialysis -- Basic chemistry of body fluids and electrolytes -- Renal physiology and the pathology of renal failure -- Clinical manifestations of chronic kidney disease -- Dialyzers, dialysate, and delivery systems -- Principles of hemodialysis -- Water treatment -- Dialyzer preparation and reprocessing -- Infection control -- Anticoagulation and heparin administration -- Access to the bloodstream -- Patient and machine monitoring and assessment -- Nutrition management -- Laboratory data: analysis and interpretation -- Diabetes and hemodialysis -- Medication problems and dialysis -- Acute kidney injury and dialysis -- Peritoneal dialysis and home dialysis therapies -- Transplantation -- Pediatric hemodialysis -- Chronic kidney disease in the elderly -- Psychosocial aspects of dialysis therapy -- Management of quality in dialysis care -- Basic math calculations -- Test taking guidelines
Includes bibliographical references and index.
Keywords: HEMODIALYSIS